Development of Teaching Module Devices Using A Differentiated Approach with An Inquiry-Based Learning Model in the Motion Kinematics Material - Mamonto, Siti Nurhaliza; Buhungo, Trisnawaty Junus; Setiawan, Dewa Gede Eka; Supartin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study aims to describe the feasibility of independent curriculum teaching modules implemented with a differentiated approach with inquiry-based learning models in a diversified learning environment and accomplish specific criteria for utilization to attain student learning outcomes. This research was carried out at SMA Negeri 1 Passi class XI-A Physics. This research uses the type of R&D (Research & Development) with a 4D development model (Define, Design, Development, and Disseminate) by Thiagarajan. Validity testing uses a validation worksheet during the expert appraisal development phase. The results of this study show that the validation of all learning tools obtained 86% to 88% in